Sosialisasi Anti Bullying Pada Murid SDN Karangrejo 03 Dan SMP-SMK Yayasan Al-Ikhwaniyah Kabupaten Jember - Suwarjana, Daya Amarta; Natus, Angelique Salsabillah Yumna Patricia; Ardian, Farhan Tri; Syarifuddin, Ahmat; Hapsari, Yusita Titi (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2024)
Anti-bullying socialization activities were carried out at SDN Karangrejo 03 and Yayasan Al-Ikhwaniyyah, Jember Regency, in response to the increasing cases of bullying in educational environments. The phenomenon of bullying that still often occurs, especially in verbal forms, requires real steps to increase awareness of students and educators about the negative impacts of this action. The methods used in this community service include initial observation, planning socialization materials, and implementing activities that include showing educational videos, interactive discussions, and ice-breaking sessions to encourage active participant involvement. The results of the activities showed an increase in participants' understanding of the importance of stopping bullying, although challenges were still found in the form of normalizing bullying behavior among students. In conclusion, this socialization succeeded in creating initial awareness that is important in building a safe and bullying-free school environment. However, to achieve long-term change, ongoing efforts are needed that involve the entire school community. Keyword: Stop Bullying, Socialization, and Children's Character Education